Santé et Big Data : l’Etat et les individus, impuissants face aux pouvoirs des réseaux - Joël Colloc (L'Espace Politique)
The use of Internet and of the social networks, lead the users to share data concerning their private life and their health. The consultation of many sites, the use of smartphones or computers leaves numerous traces on networks which are logged and indexed thanks to the identifiers of the users. These data allow to build the profile of individuals what brings social consequences and exclusion. The Big Data is defined by computer scientists and from the point of view of economists and managers, who show the advantages that companies can get from the exploitation of big repositories of data. The article presents the advantages and the limits of the use of clouds for the storage of personal data of health. Finally, elements solutions are proposed to preserve the respect of privacy.